Flow induced vibrations of a sharp edge square cylinder in the wake of a circular cylinder. (June 2017) - Tamimi, Vahid; Naeeni, Seyed Taghi Omid; Zeinoddini, Mostafa
Highlights: Experimental study of an oscillating square cylinder at the wake of a fixed circular cylinder. The lateral displacements, lift forces and pressures are recorded and analyzed. The freely mounted square cylinder displays a VIV type of response at all spacing ratios. The vortices from the upstream circular cylinder significantly affect the shedding mechanism of the downstream square cylinder. Abstract: The response of an oscillating circular cylinder at the wake of an upstream fixed circular cylinder was classified by different researchers as galloping, wake induced galloping or wake induced vibration. Furthermore it is already known that a sharp edge square cylinder would undergo galloping if it is subjected to uniform flow. In this study the influence of the wake of a fixed circular cylinder on the response of a downstream square cylinder at different spacing ratios ( S/D = 4, 8, 11) is experimentally investigated. The subject appears not to have received previous attention. The lateral displacements, lift forces and the pressure data from gauges mounted in the wake of the oscillating cylinder are recorded and analyzed. The single degree of freedom vibrating system has a low mass-damping parameter and the Reynolds number ranges from 7.7 × 10 2 to 3.7 × 10 4 . In contrast to that for two circular cylinders in tandem arrangement, the freely mounted downstream square cylinder displays a VIV type of response at all spacing ratios tested. There is no sign of galloping or wake induced galloping with the square cylinder. With increase at the spacing ratio the cross-flow oscillations decrease. It is shown that the vortices arriving from the upstream fixed circular cylinder play a major role on the shedding mechanism behind the downstream square cylinder and cause the square cylinder to shed vortices with frequencies above Strouhal frequency of the fixed square cylinder (St = 0.13). The VIV type of oscillations in the downstream square cylinder is most probably caused by the vortices newly generated behind the square cylinder.